The missing picture: accounting for sexual and gender-based violence during Cambodia’s ‘other’ conflict periods - Kochanski, Adam (International journal of transitional justice, 2020)
Local transitional justice (TJ) processes have performed an invaluable function in raising awareness about conflict-related sexual and gender-based violence. While locally-rooted praxis has been increasingly suggested as an alternative to the top-down approach to TJ, which is prone to interference, this article argues that well-intentioned local initiatives can also be distorted through discursive framing tactics that set boundaries on discussions of conflict-related events and obfuscate who can be deemed responsible. In Cambodia, this has meant a partial account of sexual and gender-based violence—one that is limited to the three-year, eight-month and 20-day rule of the Khmer Rouge, and that marginalizes survivor experiences from other episodes of the 30-year-long internal conflict. This article explores and traces the unintended consequences of this discursive frame on three local TJ efforts to address the legacy of conflict-related sexual and gender-based violence: forum theatre, women’s hearings and testimonial therapy.